Graphic user interface (GUI) of a PID controller simulator using visual basic: article / Azlinda Aznam - Aznam, azlinda (2006)
In this project, it is aimed to develop and design a graphic user interface (GUI) for water level measurement system using Visual Basic. The design is based on the hardware available in the laboratory at the Faculty of Electrical Engineering, UiTM, Shah Alam. The system was design in such a way that users are able to enter the PID parameters and display the output response of the system. The design also used the animation technique to show the flow of water. The system performance is compared to the actual experiment in term of output response generated for appropriate PID setting. This is a hope that the success of this project will be an alternative for students to conduct an experiment.